"Lost Generation" in South Sudan: A Broader Approach Toward Peace Urgently Needed. (6th March 2019) - Wild, Hannah; Fallavier, Pierre; Patel, Ronak
ABSTRACT: What began in 2013 as the eruption of a political struggle between forces loyal to President Salva Kiir, a member of the Dinka ethnic group, and then–vice president Riek Machar, a Nuer, has splintered into a multifaction conflict. A dizzying array of armed groups have entered the fray, many unmotivated by political leverage that conventionally brings parties to a conflict to the negotiating table. Two years and tens of thousands of deaths after the 2015 signing of the Agreement on the Resolution of the Conflict in South Sudan, with no substantive progress toward meetings its terms, it is unrealistic to think that Intergovernmental Authority on Development's recently announced High-Level Revitalization Forum will be sufficient to address the drivers of this conflict. Current policy proposals are poorly designed to address escalating intercommunal conflict and cattle raiding, both devastating forms of violence. As measures at the international level continue to be pursued, the conflict resolution strategy should also include a more comprehensive approach incorporating local actors in order to build momentum toward long-term stability. In this article, we highlight gaps in the current dialogue around a political solution in South Sudan, as well as domains that must be part of the next push for peace. ( Disaster Med Public Health Preparedness . 2019;13:663–671)